CHEMICAL POTENTIALS OF HARD-CORE MOLECULES BY A STEPWISE INSERTION METHOD - Maciel,Jéssica C. da S. L. (2018)
ABSTRACT A molecular simulation algorithm was implemented to calculate chemical potentials of hard-core molecular systems at high densities. The method is based on the Widom particle insertion method and the step-function character of free energy variations. The algorithm was evaluated for hard-sphere mixtures at infinite dilution approximation by varying the solute/solvent diameter ratio, for systems with reduced densities from 0.1 to 0.8. The proposed methodology was verified by comparing simulations of trimers diluted in spheres and of single-component dimer systems with results from the literature. Then, the method was applied to mixtures of hard-spheres and dimers at several conditions regarding composition, reduced density, and bond-length/diameter ratio. The results were used to validate equations of state from the literature. The proposed approach was able to obtain accurate chemical potentials for different hard-core molecular mixtures. Lower uncertainties were obtained when comparing with traditional methods, especially at high densities.